Education Systems and Inequalities International comparisons - Hadjar, Andreas; Gross, Christiane (2016)
How do education systems shape educational inequalities and differences in educational outcomes? And how do advantages and disadvantages in educational attainment translate into privileges and shortcomings in labour market and general life chances? Education systems and inequalities compares different education systems and their impact on creating and sustaining social inequalities. The book considers key questions such as how education systems impact educational inequalities along such variables as social origin, gender, ethnicity, migration background or ability and what social mechanisms are behind the links between education system and educational inequalities and provides vital evidence to inform debates in policy and reform.